2003
DOI: 10.1203/01.pdr.0000085170.44226.db
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Branching Morphogenesis: Lessons Learned from Loss-of-Function Phenotypes

Abstract: Branching morphogenesis, defined as growth and branching of epithelial tubules during embryogenesis, is a fundamental feature of renal, lung, mammary gland, submandibular gland, and pancreatic morphogenesis in mammals. Disruption of branching morphogenesis has been demonstrated to result in maldevelopment of some of these organs. Genetic studies performed in affected humans and mutant mice have implicated transcription factors, secreted growth factors, and cell surface signaling molecules as critical regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, there are similarities in the embryonic development of the kidney and lung. Both involve common processes, e.g., branching morphogenesis and common signaling pathways such as sonic hedgehog, fibroblast growth factor, and bone morphogenetic protein (17,41). These similarities raise the possibility that TAZ may be an effector in a common pathway that is involved in both lung and kidney development.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are similarities in the embryonic development of the kidney and lung. Both involve common processes, e.g., branching morphogenesis and common signaling pathways such as sonic hedgehog, fibroblast growth factor, and bone morphogenetic protein (17,41). These similarities raise the possibility that TAZ may be an effector in a common pathway that is involved in both lung and kidney development.…”
Section: Discussionmentioning
confidence: 99%
“…From the developmental point of view, the presence of ICC in pancreatic interstitium may be sustained by recent advances in understanding pancreatic morphogenesis [52][53][54] (the common embryological origin of gastrointestinal tube and pancreas). It was shown that the Sonic Hedgehog (Shh) cell-signaling pathway may direct mesoderm differentiation in the intestine and/or pancreas [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the deletion of Map2k1 is not lethal in yeast, but causes embryonic lethality in mice23. Among the interaction partners of Map2k1 is epidermal growth factor receptor, EGFR , which regulates the epidermal growth factor pathway that is crucial for cell growth and morphogenesis16.…”
Section: Resultsmentioning
confidence: 99%